The Influence of Motivation, Discipline and Work Organizational Culture on the Performance of Employees of the Economic Planning Bureau at the Secretariat General of the DPR-RI. - Muhammad Idris; Wahyu Sanjaya (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The study aims to determine whether motivation, discipline and organizational culture influence the performance of planning bureau employees at the Secretariat General of the DPR-RI. This type of research is quantitative descriptive. The sample in this study were employees of the planning bureau at the Secretariat General of the DPR-RI. A total of 90 people. This study uses primary data. Simultaneous hypothesis testing results show that motivation, discipline, and organizational culture significantly influence the performance of planning bureau employees at the Secretariat General of the DPR-RI. Testing the partial hypothesis, the results obtained that partially work motivation has a significant influence on the performance of the Planning Bureau employees at the Secretariat General of the DPR-RI. Partially there is an influence of discipline on the performance of the Planning Bureau employees at the Secretariat General of the DPR-RI. Testing the partial hypothesis, the results show an effect of organizational culture on the performance of the Planning Bureau employees at the Secretariat General of the DPR-R